Analisis Penerimaan Sistem Informasi Akademik (SIAKAD) Pada Politeknik Sains Dan Teknologi Wiratama Maluku Utara - Syahril Hasan - Politeknik Sains dan Teknologi Wiratama Maluku Utara (LPPM Universitas Bina Sarana Informatika, 2016)
Abstract - Analysis Admission Academic Information System (SIAKAD) Based on The Web Polythechinc Science and Technologi Wiratama North Maluku. Analysis of the acceptance of the Academic Information System (SIAKAD) Web-based on Polythechinc Science Andtechnologi Wiratama North Maluku. This research aims to analyze the acceptance of the Academic Information System (SIAKAD) Web Based on Polythechinc Science and Technologi Wiratama North Maluku using Technology Acceptance Mode (TAM). The use of the model of TAM because it is considered as the best concept in explaining the behavior of the user of the new information technology system. The determination of the sample is done with the sampling acidental sampling method by chance based on population present at the spread of the questionnaire. Analysis of the data using SEM (Structural Equation Modeling) with software AMOS (Analysis of Moment Popularly) version computing 22.Research Results prove that follow the hypothesis was accepted and one rejected hypothesis. The hypothesis that is received: 1) User Abilities & Skills (Test Scores) affect Perceived Ease of Use (PEOU); 2) User Abilities & Skills (Test Scores) affect the intention to Use (IS); 3) User Abilities & Skills (Test Scores) affect Perceived Usefulness (PU); 4) Perceived Ease of Use (PEOU) affect Attitude Highly Toward Using Heading (Heads Up); 5) Perceived Usefulness (PU) or the benefits of using SIAKAD Politeknik Science and Technology Wiratama affect attitude highly toward Using Heading (Heads Up) or positive attitude users SIAKAD; 6) should have toward Using Heading (Heads Up) or positive attitude users SIAKAD Politeknik Wiratama affect their interest to use SIAKAD; 7) Intention to Use (IS) or user interest SIAKAD Politeknik Science and Technology Wiratama affect Actual Usage Behavior (AUB) or usage behavior toward SIAKAD. While the hypothesis that rejected a blatant three hypothesis which stated that User Abilities & Skills (Test Scores) affect Attitude Highly Toward Using Heading (Heads Up) SIAKAD Politeknik Science and Technology Wiratama. Thus the implementation of the information system must pay attention to the factors that affect the user in the acceptance of information system.Key Words: Analysis, Acceptance, SIAKAD, TAM, SEM. Intisari - Analisis Penerimaan Sistem Informasi Akademik (SIAKAD) Berbasis Web pada Politeknik Sains dan Teknolgi Wiratama Maluku Utara. Penelitian ini bertujuan untuk menganalisis penerimaan Sistem Informasi Akademik (SIAKAD) Berbasis Web pada Politeknik Sains dan Teknologi Wiratama Maluku Utara dengan menggunakan Technology Acceptance Mode (TAM). Penggunaan model TAM karena dianggap sebagai konsep yang paling baik dalam menjelaskan perilaku user terhadap sistem teknologi informasi baru. Penentuan sampel dilakukan dengan acidental sampling yaitu metode pengambilan sampel secara kebetulan berdasarkan populasi yang hadir pada saat penyebaran kuesioner. Analisis data menggunakan SEM (Structural Equation Modelling) dengan software AMOS (Analysis of Moment Structure) komputasi versi 22. Hasil penelitian membuktikan bahwa tuju hipotesis diterima dan satu hipotesis ditolak. Hipotesis yang diterima adalah: 1) User Abilities & Skills (UAS) berpengaruh terhadap Perceived Ease of Use (PEOU); 2) User Abilities & Skills (UAS) berpengaruh terhadap Intention to Use (ITU); 3) User Abilities & Skills (UAS) berpengaruh terhadap Perceived Usefulness (PU); 4) Perceived Ease of Use (PEOU) berpengaruh terhadap Attitude Towards Using (ATU); 5) Perceived Usefulness (PU) atau manfaat penggunaan SIAKAD Politeknik Sains dan Teknologi Wiratama berpengaruh terhadap Attitude toward Using (ATU) atau sikap positif pengguna SIAKAD; 6) Attitude Towards Using (ATU) atau sikap positif pengguna SIAKAD Politeknik Wiratama berpengaruh terhadap minat mereka untuk menggunakan SIAKAD; 7) Intention to Use (ITU) atau minat pengguna SIAKAD Politeknik Sains dan Teknologi Wiratama berpengaruh terhadap Actual Usage Behavior (AUB) atau perilaku penggunaan terhadap SIAKAD. Sedang hipotesis yang ditolak adala hipotesis tiga yang menyatakan User Abilities & Skills (UAS) berpengaruh terhadap Attitude Towards Using (ATU) SIAKAD Politeknik Sains dan Teknologi Wiratama. Dengan demikian penerapan sistem informasi harus memperhatikan faktor-faktor yang mempengaruhi user dalam penerimaan sistem Informasi.Kata Kunci: Analisis, Penerimaan, SIAKAD, TAM, SEM